2019
DOI: 10.1002/jsfa.9681
|View full text |Cite
|
Sign up to set email alerts
|

Zinc application in conjunction with urea as a fertilization strategy for improving both nitrogen use efficiency and the zinc biofortification of barley

Abstract: BACKGROUND: Intensive cropping systems have caused widespread Zn deficiency, low nutritional quality of cereals and environmental problems. The aim of the microplot field experiment reported in this paper was to assess the option of using Zn in conjunction with urea fertilization in order to reduce N rate and to maintain the yield level and grain quality but minimizing environmental risks. Barley (Hordeum vulgare L.) was cultivated in a calcareous soil under semi-realistic conditions. Combinations of four Zn l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 31 publications
(36 reference statements)
3
11
0
2
Order By: Relevance
“…This positive effect of Zn and N fertilization on Zn biofortification that was observed for most of the Zn treatments has also been described in several previous experiments using ZnSO4 (ZnSul) (e.g. Gonzalez et al, 2019;Kutman et al, 2010;Xue et al, 2012). These authors suggested that grain proteins act as Zn sinks, which could explain this synergistic effect.…”
Section: Zn Availability In the Soilsupporting
confidence: 81%
See 1 more Smart Citation
“…This positive effect of Zn and N fertilization on Zn biofortification that was observed for most of the Zn treatments has also been described in several previous experiments using ZnSO4 (ZnSul) (e.g. Gonzalez et al, 2019;Kutman et al, 2010;Xue et al, 2012). These authors suggested that grain proteins act as Zn sinks, which could explain this synergistic effect.…”
Section: Zn Availability In the Soilsupporting
confidence: 81%
“…Our study, therefore, demonstrates that Zn-N coapplication can be a sustainable strategy for enhancing crop quality and yields and increasing N use efficiency in Zn-deficient soils. Gonzalez et al (2019) and Xue et al (2012) also observed this synergistic and positive effect on Zn biofortification through Zn-N co-fertilization as a result of grain proteins acting as Zn sinks. Future studies should look at whether it is possible to reduce the N rate to below the recommended rate by using Zn fertilizers in wheat.…”
Section: Effect Of N Ratementioning
confidence: 78%
“…Co‐fertilization with N also increased the Zn concentration in each part of the plant (grain, stem, and leaf) in winter wheat. This positive effect of Zn and N fertilization on Zn biofortification that was observed for most of the Zn treatments has also been described in several previous experiments using ZnSO 4 (ZnSul) ( e.g ., Kutman et al., ; Xue et al., ; Gonzalez et al., ). These authors suggested that grain proteins act as Zn sinks, which could explain this synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The absorption and mobility of Zn from the rhizosphere to the grain is dependent on different proteins and other N compounds, including amino acids and peptides ( Palmer and Guerinot , ). When Zn availability in soil was high or sufficient due to Zn foliar application to the crop, a positive effect of N was observed on Zn biofortification ( Gonzalez et al., ). A link has also been reported between the remobilization of N and Zn from senescing leaf tissues into wheat grain ( Waters et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Various authors have studied the effects of applying Zn-N combinations using inorganic sources of Zn, such as ZnO, ZnSO 4 , or Zn(NO 3 ) 2 (Cakmak et al 2010;Erenoglu et al 2011;Gonzalez et al 2019;Kutman et al 2010). All these studies have focused on the impact of applying Zn-N combinations on N and Zn concentrations in plants in just one way: N fertilization combined with soil Zn applications has a significant interaction on grain Zn and N concentrations.…”
Section: Introductionmentioning
confidence: 99%